Effect of Peginterferon or Ribavirin Dosing on Efficacy of Therapy With Telaprevir in Treatment-Experienced Patients With Chronic Hepatitis C and Advanced Liver Fibrosis: A Multicenter Cohort Study. Issue 38 (September 2015) - Janczewska, Ewa; Flisiak, Robert; Zarebska-Michaluk, Dorota; Kozielewicz, Dorota; Berak, Hanna; Dobracka, Beata; Librant-Suska, Marta; Lojewski, Wladyslaw; Jurczyk, Krzysztof; Musialik, Joanna; Postawa-Klosińska, Barbara; Wroblewski, Jacek; et al.
Abstract : Abstract: We investigated the safety, efficacy, and impact of ribavirin and peginterferon dose reduction on complete early virologic response and sustained virologic response (SVR) to triple therapy with telaprevir in treatment-experienced patients with advanced liver fibrosis. Treatment was initiated for 211 patients who failed treatment with peginterferon and ribavirin, with bridging fibrosis (F3, n = 68) or cirrhosis (F4, n = 143), including 103 (49%) null-responders (NR), 30 (14%) partial responders (PR), and 78 (37%) relapsers (REL). Impaired liver function (ILF) platelets <100, 000/mm 3 or albumin <35 g/L were present in 40 patients. The distribution of hepatitis C virus subtypes was: 1a, 1b, or 1, with undetermined subtype for 10 (5%), 187 (89%), and 14 (6%) patients, respectively. Treatment was started with peginterferon alpha-2a or alpha-2b, ribavirin, and telaprevir at standard doses. The overall SVR24 rate was 56% and was lower in cirrhotic patients (NR: 35%, PR: 40%, and REL: 63%, respectively) than in patients with bridging fibrosis (NR: 50%, PR: 75%, and REL: 75%, respectively). The lowest probability of SVR24 was in NRs with ILF (26%). The SVR24 rate significantly decreased in NRs receiving <60% vs >60% of the total ribavirin dose (23% vs 44%, respectively) or <80% vs >80% of the total ribavirin dose (33% vs 48%, respectively). A significant SVR24 decrease was noted subsequent to a total peginterferon dose reduction, both when comparing patients who received <60% vs >60% of the total dose (NR: 0% vs 44%; REL: 33% vs 68%) and patients who received <80% vs >80% of the total dose (NR: 17% vs 50%; REL: 46% vs 71%). Serious adverse events were observed in 31 patients (15%). Deaths occurred in 4 patients. All of the deceased subjects were cirrhotic members of the ILF (baseline serum albumin level <35 g/L and/or platelet count <100, 000/mm 3 ) group. Ribavirin dose reduction did not affect efficacy in REL but did in NR. Peginterferon dose reduction decreased the SVR24 rate for all groups, particularly in prior NR. ILF increased the risk of fatal complications with a low probability to achieve SVR24. One solution might be to provide wide and early access to novel, efficient, and safe interferon-free combinations to treatment-experienced patients, particularly those with liver cirrhosis.